Implementation of Social Rehabilitation Program for People with Disabilities in Makassar City - Arpin, Arpin; Rifdan, Rifdan; Niswaty, Risma (International Journal of Humanities, Education, and Social Sciences, 2025)
The aims of this study to examine and analyse the form of implementation of social rehabilitation programs for people with disabilities in Makassar City; to identify and analyse factors that influence the implementation of social rehabilitation programs for people with disabilities in Makassar City; and to analyse in depth the strategy for developing the implementation of social rehabilitation programs for people with disabilities in Makassar City. The informants in this study were key informants and ordinary informants. Data collection techniques used through observation, interviews, and documentation studies. In data analysis, researchers used qualitative data analysis techniques. Based on the results of the study, the implementation of social rehabilitation programs for people with disabilities in Makassar City, as seen based on policy implementation indicators, namely communication indicators, disposition resources, and bureaucratic structures in general, has been running well. The determinant factors for the implementation of social rehabilitation programs for people with disabilities in Makassar City are human resource capacity factors and budget factors. The human resource capacity factor (HR) is the main key to the success of the implementation of social rehabilitation programs for people with disabilities in Makassar City.